2006
DOI: 10.1620/tjem.210.37
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Internet Access in Adult Patients with Atopic Dermatitis in Japan

Abstract: The Internet has provided open access to health-and disease-related information for people with chronic diseases. Atopic dermatitis (AD) is mostly chronic, and the treatment of AD often requests some self-management such as skin care. For this situation, adult AD patients may have a motive of obtaining information on AD from various sources such as the Internet. Although the status of Internet access among AD patients has not been thoroughly investigated, knowledge about this status may be useful to understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The current status needs further investigations in each country. 193,194 The health systems and possibilities are differing in each countries. Personal contact and the structured programmes such as the educational schools show the most benefit.…”
Section: Forms Of Educational Intervention Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current status needs further investigations in each country. 193,194 The health systems and possibilities are differing in each countries. Personal contact and the structured programmes such as the educational schools show the most benefit.…”
Section: Forms Of Educational Intervention Toolsmentioning
confidence: 99%
“…Internet access is not common everywhere and the information is not necessarily credible among adult patients. The current status needs further investigations in each country 193,194 …”
Section: Educational Interventions For Atopic Eczemamentioning
confidence: 99%
“…One study on dermatology outpatients in the USA noted that almost two‐thirds of respondents reported having Internet access, and slightly over half of them used the Internet to search for medical information 17 . In another study on Japanese atopic dermatitis outpatients, 94% of respondents replied that they had access to the Internet, and 29% searched online for information on general health‐related issues and atopic dermatitis 18 . An Iranian study on dermatology outpatients showed that 36% had Internet access, just over 4% used the Internet to search for information on their skin condition, and only 0.5% used an academic website 9 …”
Section: Discussionmentioning
confidence: 99%